The positioning of the 'Conti' brand in enhancing customer's acceptance and awareness: A case of Continental Sime Tyre Malaysia (CSTM) Sdn. Bhd. / Noraishah Idris (Faculty of Business Management, 2005)
In facing the development era of technology and industrial market, the business world is getting more competitive and aggressive by the day. Business compete with each other in order to boost sales by trying to come up with the best advertisement, promotional tools, good customer strategies and other tools that available. Since being introduced to the public, Conti brand have been among the top brands that people eager to get in the market. However, in order to maintain CSTM positions in the market, continuous studies and strategies must be develop and implement in order to achieve it. As far as we can see, most of the tyre manufacturers are not so focusly on promotional tools, but more on sponsoring big events in order to capture the market. But then, it doesn't mean that promotional tools are not necessary in this field. Therefore, the objectives of this study is to (1) identify some of the best tools that can be used to maintain longer in the market, (2) explore whether CST brand is strong enough in the market to make consumers aware and accept the product, (3) to study the circumstances that may assist in creating awareness among customers, (4) to know what are the expectations of customers toward products offered by CSTM, and (5) last but not least; to develop few of the ideas in increasing the sales and trying to be the market leader longer. This paper consists of 5 chapters that explain the subject matter in the stages. Chapter 1 discussing on the introduction and background of the study. Chapter 2 explains the literature review, which relate to the studied and. For chapter 3, theoretical framework that acts as a guide to the research flow and process. Research methodology is explained, which consist of methods and sampling techniques to be used on chapter 4. Chapter 5 is derived from the information obtain from respondents to analyse and interpret the data from chapter 4. And finally, chapter 6 contain summary of results and findings, which explains conclusions and recommendations.